2010
DOI: 10.1177/0269216310371414
|View full text |Cite
|
Sign up to set email alerts
|

An exploration into the palliative and end-of-life experiences of carers of people with Parkinson’s disease

Abstract: Although most people with Parkinson's disease are cared for in the community, little is known about family members' lived experiences of palliative or end-of-life care. The aim of this study was to explore former carers' lived experiences of palliative and end-of-life care. In total, 15 former family caregivers of patients who had died with Parkinson's disease were interviewed using a semi-structured topic list. Findings indicated that some palliative and end-of-life care needs had not been fully addressed. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 18 publications
4
114
0
5
Order By: Relevance
“…Carers undertake proactive information searching, and perceive themselves as acting as a go between for the various services involved in the care situation to compensate for a perceived lack of communication between these services (Hasson et al, 2010).…”
Section: Everyday Choicesmentioning
confidence: 99%
“…Carers undertake proactive information searching, and perceive themselves as acting as a go between for the various services involved in the care situation to compensate for a perceived lack of communication between these services (Hasson et al, 2010).…”
Section: Everyday Choicesmentioning
confidence: 99%
“…These symptoms can complicate decision making with regards to end-of-life care 1 2. There has been an increasing recognition that people with PD may benefit from specialist palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers' support needs can be viewed as a spectrum of needs, including practical, spiritual, psychosocial, informational, emotional, and physical support needs, as adapted from the supportive care needs framework model for caregivers of cancer patients (Fitch, 1994). A number of studies have shown that the need for information is a top priority among caregivers of persons with dementia (Muangpaisan et al, 2010;Wackerbarth & Johnson, 2002), stroke (Hare, Rogers, Lester, McManus, & Mant, 2006;Kim & Moon, 2007;MacIsaac, Harrison, & Godfrey, 2010;Mak, Mackenzie, & Lui, 2007;), spinal cord injury (SCI; Meade, Taylor, Kreutzer, Marwitz, & Thomas, 2004;Post, Bloemen, & de Witte, 2005), traumatic brain injury (TBI; Arango-Lasprilla et al, 2010;Blake, 2008, Rotundi, Sinkule, & Spring, 2005Sander, Clark, Atchison, & Rueda, 2009), Parkinson's disease (PD; Hasson et al, 2010;Kristjanson, Aoun, & Oldham, 2006;Thomas & Sweetnam, 2002), and multiple sclerosis (MS; Corry & While, 2009;Kersten et al, 2000;Koopman, Benbow, & Vandervoort, 2006;Kristjanson et al, 2006). In general, caregivers of persons with chronic disease have been shown to desire two types of information: general information about the medical condition of the care recipient and specific, understandable information tailored to their situation.…”
Section: Introductionmentioning
confidence: 99%